Enrico Fermi a Firenze Le «Lezioni di Meccanica Razionale» al biennio propedeutico agli studi di Ingegneria: 1924-1926 - Casalbuoni, Roberto; Frosali, Giovanni; Pelosi, Giuseppe (I libri de «Il Colle di Galileo», 2014)
Enrico Fermi, Nobel Prize for Physics in 1938, taught at the Royal University of Florence. Fermi's stay in Florence was short and only lasted two academic years (1924-25 and 1925-26); during those years, he taught "Mathematical Physics" and "Rational Mechanics" courses. This volume contributes to the reconstruction of this quite unknown period of Fermi's life, marked however by the publication of the Fermi statistics, which is also the foundation of the physics of semiconductors, and therefore of modern electronics. The text also features Enrico Fermi's "Lessons of Rational Mechanics" to Science students and to students from the two-year preparatory course for Engineering studies during the aforementioned time span. The topics Enrico Fermi addressed in his lectures include kinematics and point dynamics, kinematics and statics of rigid systems and system statics in general. Lastly, the lessons contain «Lagrangia»'s equations and some elements of hydromechanics. This book is the first of a series of publications associated with the magazine «Il Colle di Galileo» by Firenze University Press.